Management Accounting Practices and Performance of Micro, Small and Medium Enterprises in Makassar City - Nurhidayah; Wahyuni (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2021)
The purpose of this study is to determine the effect of management accounting practices on the performance of micro, small, and medium-sized enterprises (MSMEs) in Makassar City. This study used a survey method, in which information is gathered from respondents. Quantitative variables were explored, and the data collection technique incorporated a perceptual approach in the form of a questionnaire to ease measurement. The data were gathered through the use of questionnaires sent to randomly selected respondents. This study was conducted at Makassar City's MSMEs. After obtaining the data, multiple regression analysis was used to conduct the analysis and hypothesis testing, and the results were empirical findings. The study's findings indicated that management accounting procedures based on a budgeting system approach had a statistically significant effect on the performance of MSMEs at the 5% level. Simultaneously, the cost system approach and performance assessment system have a 10% effect on the performance of MSMEs. This research demonstrates that sound management accounting methods can significantly boost the performance of MSMEs, particularly in Makassar City. This finding is consistent with the contingency theory, which states that a corporation requires the appropriate strategy to increase corporate/business performance. Among the appropriate strategies is the implementation of sound management accounting processes.